Advertisement call of the Colombian Horned Frog Ceratophrys calcarata (Anura, Ceratophryidae) - Pérez-González, José Luis; Lamadrid-Feris, Faride; Vargas-Salinas, Fernando; Rueda-Solano, Luis Alberto (Zootaxa, 2023)
N/A